2013
DOI: 10.1016/j.enpol.2013.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the international reduction pledges on long-term energy system changes and costs in China and India

Abstract: We analyze long-term impacts of the international pledges for China and India. We compare a least-cost pathway with a pathway starting from the Copenhagen pledges. Postponing mitigation action implies much higher cumulative mitigation costs. Postponing increases fossil fuel dependence and requires deeper long-term reductions. Countries differ mainly due to different periods of rapid economic change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 37 publications
(34 reference statements)
1
20
0
Order By: Relevance
“…Current global and regional studies [13,23,74,94,95] do not expect CCS to be applied in China before 2030 in an appreciable way either. In addition, a number of modelling studies expect the substantial deployment of CCS to take place as early as in the 2030s [12,94].…”
Section: Overall Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current global and regional studies [13,23,74,94,95] do not expect CCS to be applied in China before 2030 in an appreciable way either. In addition, a number of modelling studies expect the substantial deployment of CCS to take place as early as in the 2030s [12,94].…”
Section: Overall Results and Discussionmentioning
confidence: 99%
“…They developed long-term energy scenarios, exploring the role played by CCS in a macro-economic optimised environment (for example, in [12][13][14][15][16], which modelled the Chinese energy system; in [17][18][19][20], which analysed China as part of long-term energy scenarios for Asia, and in [8,[21][22][23], which modelled China as one of several regions within world energy models). In addition,…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that greenhouse gas (GHG) emissions reductions in Asia 14,15 and Africa 16,17 would increase the cost of kerosene and LPG. However, these studies do not explore compensatory policies that could counteract these effects, and assess only a limited set of climate mitigation scenarios.…”
mentioning
confidence: 99%
“…This model indeed adopts a dynamic, multi-region and multi-sector 2 The Intergovernmental Panel on Climate Change (IPCC) scenarios that belong to category II aim for a radiative forcing between 3 and 3.5 W/m 2 to a CO 2 -equivalent concentration between 490 and 535 ppm and an increase in the global temperature between 2.4 and 2.8°C above the pre-industrial level. 3 A notable exception is a recent paper by Lucas et al (2013) who find that ''postponing mitigation action increases the lock-in in less energy-efficient technologies and results in much higher cumulative mitigation costs''. But this assessment is run at a 2050 horizon, considers a ?2°C temperature target and adopts bottom-up models that fail to capture the complexity of macroeconomic interplays driven by the adjustment of energy systems.…”
Section: Introductionmentioning
confidence: 92%